2012
DOI: 10.2463/mrms.11.291
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Elastography for Staging Liver Fibrosis in Chronic Hepatitis C

Abstract: Purpose: We evaluated the use of magnetic resonance (MR) elastography (MRE) for staging liverˆbrosis in patients with chronic hepatitis C and compared the ability of MRE and serumˆbrosis markers for discriminating each stage ofˆbrosis.Methods: We evaluated 114 patients with chronic hepatitis C in whom the pathological brosis stage was determined (ˆbrosis stage 0 [F0], 3; F1, 15; F2, 28; F3, 25; and F4, 43). All patients underwent MRE using a 1.5-tesla MR system and pneumatic driver system. We measured stiŠness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
3
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 33 publications
9
79
3
4
Order By: Relevance
“…As MRE is proving to be an accurate and reliable test, many single etiology studies with MRE in diseases such as hepatitis B, hepatitis C, alcoholic liver disease and NASH have emerged [141,[146][147][148][149], and all show high performance (accuracy [ 0.90) of MRE in the detection of fibrosis. Large population studies are still lacking.…”
Section: Magnetic Resonance Elastography (Mre)mentioning
confidence: 99%
See 1 more Smart Citation
“…As MRE is proving to be an accurate and reliable test, many single etiology studies with MRE in diseases such as hepatitis B, hepatitis C, alcoholic liver disease and NASH have emerged [141,[146][147][148][149], and all show high performance (accuracy [ 0.90) of MRE in the detection of fibrosis. Large population studies are still lacking.…”
Section: Magnetic Resonance Elastography (Mre)mentioning
confidence: 99%
“…The total costs associated with the LB alone strategy for men and women were US $195,169 and US $214,760, respectively. The authors of this study concluded that in clinical settings where testing is required prior to treatment, FT alone is more effective and less costly than LB although the actual cost savings appear minimal and may have less value because of the decreased accuracy of FT [146]. The cost-effectiveness of TE performed annually was found to be better than LB performed every 7 years in the evaluation of liver fibrosis in patients with HIV/HCV coinfection [157].…”
Section: Cost-effectiveness Of Non-invasive Markers For Liver Fibrosismentioning
confidence: 99%
“…Respective cut-off values for the APRI, UTE, and MRE were 0.5, 5.2, and 3.2 kPa for significant fibrosis (!F2) and 2.0, 12.9, and 4.6 kPa for cirrhosis (F4). 6,7 Accuracy of fibrosis staging was com- , had an APRI of 1.65, indicating significant fibrosis, but not cirrhosis. A value of 16.0 kPa, by UTE, indicated cirrhosis, whereas noncirrhosis, but significant fibrosis, were suggested by a 3.6-kPa value by MRE.…”
Section: Bayesian Prediction For Liver Fibrosis Staging: Combined Usementioning
confidence: 99%
“…16 It is believed that CHB has a tendency to involve more advanced focal necrosis and inflammatory cell infiltration than CHC. Unfortunately, the number of MRE studies is limited for groups with a single etiology, such as CHC, 13 CHB, 17,18 alcoholic hepatitis, 19 nonalcoholic steatohepatitis (NASH), 20,21 and Gaucher disease. 22 Accordingly, it appears that more evidence would have to be collected using subjects with single-etiology liver disease to establish the use of MRE in clinical settings.…”
Section: Introductionmentioning
confidence: 99%